Thymoquinone inhibits tumor growth and induces apoptosis in a breast cancer xenograft mouse model: the role of p38 MAPK and ROS. - Chern Chiuh Woo (PLoS ONE, 2013)
Due to narrow therapeutic window of cancer therapeutic agents and the development of resistance against these agents, there is a need to discover novel agents to treat breast cancer. The antitumor activities of thymoquinone (TQ), a compound isolated from Nigella sativa oil, were investigated in breast carcinoma in vitro and in vivo. Cell responses after TQ treatment were assessed by using different assays including MTT assay, annexin V-propidium iodide staining, Mitosox staining and Western blot. The antitumor effect was studied by breast tumor xenograft mouse model, and the tumor tissues were examined by histology and immunohistochemistry. The level of anti-oxidant enzymes/molecules in mouse liver tissues was measured by commercial kits. Here, we show that TQ induced p38 phosphorylation and ROS production in breast cancer cells. These inductions were found to be responsible for TQ's anti-proliferative and pro-apoptotic effects. Moreover, TQ-induced ROS production regulated p38 phosphorylation but not vice versa. TQ treatment was found to suppress the tumor growth and this effect was further enhanced by combination with doxorubicin. TQ also inhibited the protein expression of anti-apoptotic genes, such as XIAP, survivin, Bcl-xL and Bcl-2, in breast cancer cells and breast tumor xenograft. Reduced Ki67 and increased TUNEL staining were observed in TQ-treated tumors. TQ was also found to increase the level of catalase, superoxide dismutase and glutathione in mouse liver tissues. Overall, our results demonstrated that the anti-proliferative and pro-apoptotic effects of TQ in breast cancer are mediated through p38 phosphorylation via ROS generation.